Engklek: A Traditional Play to Improve Children’s Cognitive - Pahenra Pahenra; Winarni Winarni; Siti Salma; Roni Amaludin; Waode Sari Amalia (AWLADY : Jurnal Pendidikan Anak, 2021)
ABSTRACT This research is motivated by the discovery of children's cognitive abilities that have not developed optimally, this is due to learning activities in classical settings, the lack of fun learning techniques, the ability to use learning media, playing activities while learning is very lacking so that children become bored, lack focus in following learning. The purpose of this study was to improve early childhood cognitive abilities through traditional game media in group B TK AL-Aqsho, Lamomea Village, Konda District, South Konawe Regency. This type of research is classroom action research. The results showed that the acquisition of children's completeness skills increased at each stage where the acquisition of children's pre-action completeness was 31.58%, increased in cycle 1 by 63.16% and in cycle 2 increased by 78.94% with minimum completeness criteria. (KKM) which is determined from the school, namely 75%. So it can be concluded that the implementation of learning activities through the traditional crank game can improve the cognitive abilities of children in group B in Al-Aqsho Kindergarten, Lamomea Village, Konda District, South Konawe Regency. Therefore, based on this research, it is hoped that the traditional crank game can be used as a reference for early childhood teachers to apply it or researchers to become a reference in developing the results of this study further.Keywords:   Cognitive abilities; early childhood; traditional game of crank.ABSTRAK Penelitian ini dilatarbelakangi oleh ditemukannya kemampuan kognitif anak yang belum berkembang secara optimal, hal ini disebabkan aktivitas pembelajaran dalam setting klasikal, teknik pembelajaran yang kurang menyenangkan, kemampuan menggunakan media pembelajaran, aktivitas bermain sambil belajar sangat kurang sehingga anak menjadi bosan, kurang fokus dalam mengikuti pembelajaran. Tujuan penelitian ini adalah untuk meningkatkan kemampuan kognitif anak usia dini melalui media permainan tradisional pada kelompok B TK AL-Aqsho Desa Lamomea Kecamatan Konda Kabupaten Konawe Selatan. Jenis penelitian ini adalah penelitian tindakan kelas. Hasil penelitian menunjukkan bahwa perolehan ketuntasan ketuntasan anak meningkat pada setiap tahapan dimana perolehan ketuntasan pra tindakan anak sebesar 31,58%, meningkat pada siklus 1 sebesar 63,16% dan pada siklus 2 meningkat sebesar 78,94% dengan kriteria ketuntasan minimal. (KKM) yang ditentukan dari sekolah yaitu 75%. Sehingga dapat disimpulkan bahwa pelaksanaan kegiatan pembelajaran melalui permainan tradisional engkol dapat meningkatkan kemampuan kognitif anak kelompok B di Taman Kanak-kanak Al-Aqsho, Desa Lamomea, Kecamatan Konda, Kabupaten Konawe Selatan. Oleh karena itu, berdasarkan hasil penelitian ini diharapkan permainan engkol tradisional dapat dijadikan acuan bagi guru PAUD untuk mengaplikasikannya atau peneliti untuk menjadi acuan dalam mengembangkan hasil penelitian ini lebih lanjut.Kata Kunci:   Kemampuan kognitif; anak usia dini; permainan tradisional engklek.